The impacts of within-stream physical structure and riparian buffer strips on semi-aquatic bugs in Southeast Asian oil palm - Harianja, Martina F.; Luke, Sarah H.; Barclay, Holly; Chey, Vun K.; Aldridge, David C.; Foster, William A.; Turner, Edgar C. (Frontiers in Forests and Global Change, 2024)
Despite the diverse ecosystem services that forested stream margins (“riparian buffer strips”) can provide in agricultural landscapes, understanding of their biodiversity impacts in the tropics is lacking. Stream invertebrates support many ecosystem functions and several groups are valuable bioindicators of environmental conditions. Semi-aquatic bugs (insects in Hemiptera that inhabit the water surface) are important within the aquatic food chain, acting as predators of other invertebrates and prey for larger animals. Since they inhabit the water surface, semi-aquatic bugs are potentially valuable indicators of within-stream health. Focusing on the impacts of conditions at the small-scale, we investigated how within-stream physical structure and the presence of riparian buffer strips affected the abundance, total biomass, richness, and community composition of semi-aquatic bugs in oil palm plantations in Sabah, Malaysia. We also assessed the effects on the proportion of juveniles and females of Ptilomera sp. (a common genus). Our focus on the small-scale make findings applicable for management both within smallholder and largescale plantations. At the small-scale (10-m transect), oil palms streams with riparian buffers contained twice as many semi-aquatic bugs as those without (average richness in streams with buffers 3.55 (SE±0.42) compared to 1.40 (SE±0.22) in streams without). We found a total of 14 morphospecies in streams with buffers, compared to just seven in those without. There was no difference in total biomass or the proportion of female Ptilomera sp. in streams with or without buffers. There was a significantly higher abundance of semi-aquatic bugs in streams with wider wetted width, more isolated pools, shallower slopes, and lower percentage of deadwood. The proportion of juveniles was higher in streams with higher canopy openness, higher percentage of deadwood, lower percentage of pebbles, and narrower wetted widths. This study demonstrates that small-scale differences in stream conditions within oil palm can influence semi-aquatic bugs, opening up the possibility that oil palm management could be tailored to improve environmental conditions for stream communities. As our findings are based on only a few streams and at measurements collected at a single time-point, more studies are needed to validate what we have found.